Efektivitas promosi kesehatan pencegahan Covid-19 dengan CTPS - Rakhmawati, Windy; Hermayanti, Yanti; Amita, Dzikra Fitria; Abas, Latifa Hidayani; Ummah, Arief Khoerul; Mufida, Mufida; Risminda, Nestia; Nabilah, Nurul Azmi; Amalia, Pandu Rifqi; Obara, Septa; Wirahandayani, Marthalisa (Jurnal Pengabdian Harapan Ibu (JPHI), 2021)
COVID-19, the infectious disease caused by SARS-CoV-2, has emerged as a global health crisis and pandemic. Children are very susceptible to disease transmission because their immune system is not yet perfect. To achieve the spread and transmission of this virus, interventions are needed across the population. The promotion of hand washing in children is needed to increase children's knowledge about preventing covid-19 by washing hands with soap. The purpose of this study is to give Indonesian children additional education about handwashing with soap and to make them be able to demonstrate good and correct hand washing. The health education is conducted by giving lecture to the children and showing them videos in the end of the sessions. After that, an evaluation of the health education is carried out by giving the children pre-test and post-test designs. The result of the study showed that 96% children (49 of 51) who attended the health education experienced an increase in their post-test results. This indicated that the content of the health education can be easily understood by most of the children. A good learning process requires several supporting factors such as careful preparation, interactive way of delivering instruction, and good team coordination. In order to monitor the application of the knowledge obtained in the health education, it is necessary to carry out continuous educative activities so that hopefully there will be an increase in the health quality of Indonesian children. Keywords : Covid-19, Education, Hand Washing Steps